Analysis of the adhesive thickness effect on failure pressure of metal/composite hybrid joints in pressurized blister tests. (January 2023) - Miranda, B.M.; Reis, J.M.L.; da Costa Mattos, H.S.
Abstract: Composite repairs are increasingly being used to restore the work capability of pipelines with through-wall defects by corrosion. In this context international standards, such as ISO and ASME are the references to design this kind of repair and to qualify such systems. The referred standards do not take into account the adhesive layer thickness (h) on the model for the calculation of the failure pressure (Pcr ), as well as for the calculation of the energy release rate (γ). In this work an experimental investigation evidences the influence of the adhesive thickness on the failure pressure. In order to achieve these results, pressurized blister tests were performed in which the geometrical parameter (h) varied from 0, 5 mm to 2, 0 mm. Ultimately, an empirical model to calculate Pcr as when the critical energy release rate (γLCL ) is a function of the adhesive layer thickness was proposed.